Tecnologia educacional: realidade aumentada como recurso pedagógico para docentes dos anos iniciais do ensino fundamental - Borborema, Silvana Moreira Tavares (2024)
Digital Technologies have revolutionized daily life and education, driving the emergence of Education 4.0 and necessitating that educators continuously update their skills to explore new pedagogical methodologies. This new pedagogical approach involves integrating digital Technologies as didactic resources. Among these technologies, augmented reality was chosen due to its potential as a pedagogical tool and it is, still, unexplored application in the classroom. Augmented reality is a solution that allows the interaction of virtual objects in the real world through electronic devices. With this in mind, the general objective of this research was defined as contributing to the development of digital competence of elementary school teachers, aiming to encourage the use of augmented reality as a pedagogical resource and analyze their perceptions (motivation, effectiveness, usability, safety and confidence, ease, and preference of use of the presented applications) after applying a workshop. To achieve this objective, specific goals were set: to characterize the profile of the teachers at Gabriela Mistral Municipal School; to understand the level of teachers' comprehension regarding educational technologies and augmented reality; structure, develop, and conduct a training workshop on augmented reality; to analyze teachers' perceptions of this technology. Methodologically, this research is predominantly qualitative, applied, exploratory and descriptive objectives. The study's structure is based on the case study and action research technique. Initially, it was necessary to understand, through a systematic literature review, how teachers are prepared for the pedagogical use of augmented reality and to define relevant terms. For data collection, two semi-open questionnaires and participant observation during the workshop were used. In the workshop, six educational augmented reality applications were explored. The results of the teachers' perceptions were positive in the evaluated dimensions, and the highest-rated applications were Quiver, Hope, Sólidos RA, and App Augmented Reality. However, all presented applications have potential for academic use. This study aimed to promote and encourage the use of augmented reality technology as a pedagogical resource, providing teachers with an understanding of its potential in teaching and learning. Furthermore, it demystified its use by presenting practical examples of application, helping teachers feel more confident in including augmented reality in their teaching methods. It was concluded that the lack of available mobile devices is the biggest limitation for the implementation of augmented reality as a pedagogical resource in the early years of elementary school. For this reason, many teachers prefer to adopt methodologies that do not depend on digital technologies.